PENGARUH ASPEK SDM DAN DUKUNGAN DARI MANAJER TERHADAP KINERJA SISTEM INFORMASI ELSA ADPS DI BANDAR UDARA HANG NADIM BATAM - Mesri Silalahi (Computer Based Information System Journal, 2015)
Hang Nadim Airport Batam using a system that is ELSA ADPS. This system used since 2012 to manage the news and then send it to the cost of each unit and airports that require. This study aimed to determine the effect on the performance aspects of human resources information systems, the effect of the support of the managers of the system performance information, as well as simultaneously influence aspects of human resources and support from the manager to the performance information system ELSA ADPS. Collecting data by distributing questionnaires to all employees Hang Nadim airport in Batam using ELSA ADPS information system with descriptive data analysis and verification. The findings in this research that there is a positive and significant impact on the performance aspects of the human resources information system ELSA ADPS, there is a positive and significant impact on the Performance Manager Support of Information Systems ELSA ADPS, there is a positive and significant influence jointly between aspects of HR and support from the manager to the performance information system ELSA ADPS.